2006
DOI: 10.1530/eje.1.02073
|View full text |Cite
|
Sign up to set email alerts
|

The octreotide test dose is not a reliable predictor of the subsequent response to somatostatin analogue therapy in patients with acromegaly

Abstract: In many centres, a test dose (TD) of octreotide is administered before commencing somatostatin analogue therapy (SAT), although the merits of this procedure are uncertain. We have analysed the value of the GH response to a TD in predicting the efficacy of subsequent SAT in 47 patients with acromegaly (25 male, median age 51 years, range 20-82). The primary goal of SAT was a mean GH of , 5 mU/l. Median baseline GH was 19.3 mU/l (2.2-233 mU/l) and with the TD fell by 78% (35 -98%) to a nadir of 4.2 mU/l (, 0.3-8… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
19
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 27 publications
(22 citation statements)
references
References 25 publications
2
19
0
1
Order By: Relevance
“…As already reported [34][35][36][37], results of SA as primary or adjuvant treatment were not different. In contrast to what recently reported [38], but in agreement with others [39], acute octreotide administration was useless in predicting response to long-term treatment. Owing to the large prevalence of responsiveness to SA in acromegalic population and the very little difference in post-test probability as compared to pre-test one, it seems thus better to evaluate results of a short (3-6 months) treatment, that were convincingly reported to predict reliably the results of chronic treatment [34,35].…”
Section: Discussionsupporting
confidence: 85%
“…As already reported [34][35][36][37], results of SA as primary or adjuvant treatment were not different. In contrast to what recently reported [38], but in agreement with others [39], acute octreotide administration was useless in predicting response to long-term treatment. Owing to the large prevalence of responsiveness to SA in acromegalic population and the very little difference in post-test probability as compared to pre-test one, it seems thus better to evaluate results of a short (3-6 months) treatment, that were convincingly reported to predict reliably the results of chronic treatment [34,35].…”
Section: Discussionsupporting
confidence: 85%
“…After acute octreotide administration, GH levels fall in 50-65% of patients [54][55][56][57][58][59][60]. The criteria used to define the response to acute octreotide administration and the chronic response to somatostatin analogue therapy vary among studies.…”
Section: Other Testsmentioning
confidence: 99%
“…It has been suggested that, in patients with acromegaly, octreotide treatment reduces circulating IGF1 more than anticipated from the suppression of the endogenous GH secretion, and several groups have commented on this phenomenon (10,(26)(27)(28). These findings suggest that octreotide action is not confined to the suppression of GH secretion, but that it may also have a direct effect on IGF1 generation.…”
Section: Introductionmentioning
confidence: 99%